Bioethanol Production from Agricultural Waste Biomass as a Renewable Bioenergy Resource in Biomaterials - Sharif, Hossain; Abu Saleh, Ahmed; Aishah, Salleh; Amru Nasrulhaq, Boyce (Springer-Verlag Berlin Heidelberg, 2008)
Biomass is a renewable energy resource with high potential fuel source for the creation of steam and electricity, transportation fuel, medicinal manufacturing industries as well as a solvent in the laboratory. The more efficient use of biomass (derived bioethanol) is demanded to solve the global crisis such as depletion of fossil fuel and global warming (greenhouse gas emissions). It is presently estimated to contribute of the order 10-14% of the world energy supply. Demand for biomass-derived ethanol could be significant if ethanol became oxygenate of choice. Biomass derived biofuel such as bioethanol is increasingly applied for automotive purposes. They have, however, a relatively low efficiency in converting solar energy into automotive power. Manufacturers of proprietary medicines defended the use of ethanol by claiming that it was added to prevent their products from spoiling and freezing. In this study we mentioned the biomass preparation and fermentation techniques for bioethanol production using yeast (e.g. Saccharomyces cerevisiae) and reviewed results from different agricultural waste biomass (algae, fruit and fish, chicken). We found fruit (pineapple) biomass was higher and easier to extract than algae and fish biomass.